PERAN ORANG TUA DALAM PEMBENTUKAN KARAKTER RELIGIUS SISWA KELAS V DI SD NEGERI 3 PURWAWINANGUN - Papat Siti Fatimah; Nana Sutarna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The role of parents in the formation of students' religious character is important to create a nation's generation that has good character in accordance with the Shari'a and the provisions of Islam. The purpose of this research is to explain how the role of parents in the formation of students' religious character at SD Negeri 3 Purwawinangun. This research uses a qualitative method with a descriptive research design descriptive research design. Data collection techniques in this study used observation, interviews, questionnaires, and documentation. Data analysis techniques using Milen and Huberman model includes data display, and conclusion drawing (verification). The results of this study indicate that parents have an important role in the formation of a good religious character. To form a good religious character it can be done by doing good habituation at home. Besides in addition, in order to support the process of forming the religious character students, SD Negeri 3 Purwawinangun has also implemented a school religious program, which aims to form good habits of students at school good habits of students at school.